Konsep Maslahah di Sisi Wahbah Al- Zuhayli (1932-2015): Satu Penilaian: The Concept of Maslahah According to Wahbah al-Zuhayli (1932-2015): An Assessment - Kamar, Izal Mustafa (Jurnal Fiqh, 2021)
Over the past few years, there have been renewed interests from scholars and researchers to study on maqāṣid and maṣlaḥah from various aspects and perspectives. Such interests have opened up previously unexplored avenues of research on maqāṣid. Notwithstanding these benefits, there arec onsiderable confusions-whether intentional or otherwise-in some of these writings in understanding and implementing key principles of maqāṣid and maṣlaḥah. One of the main reasons of the confusion is the inability to comprehend a key principle in which the nuṣūṣ is in total harmony with the higher objectives of the law. Failure to understand this fundamental principle has resulted in confusion, as proponents of such ideas would propose either disregarding/discrediting the nuṣūṣ or reinterpreting it and only considering the objectives behind the text, as a solution to mitigate “contradictions” which they assume occurred. Hence, this article aims to identify and explain the maṣlaḥah framewor according to the ‘Ahl Sunnah wa al-Jamāʿah through the writings of Wahbah al-Zuḥaylī. It analyzes the relationship between maṣlaḥah and nuṣūṣ, as well as how, according to the ‘Ahl Sunnah, nuṣūṣ should be used as a yardstick (miʿyār) when making religious decisions. One of the key findings in this study is that that there are no contradictions between maṣlaḥah and nuṣūṣ. This study employs a qualitative method to understand key concepts of maqāṣid and maṣlaḥah according to the ‘Ahl Sunnah by collecting data from various data points. It utilizes both the inductive and deductive methods to comprehend key concept of maqāṣid and maṣlaḥah, as well as to identify the maṣlaḥah framework through the writings of Wahbah al-Zuḥaylī.